Infrared–metabolomics approach in detecting changes in Andrographis paniculata metabolites due to different harvesting ages and times. (24th November 2014) - Yusof, Nur A'thifah; Isha, Azizul; Ismail, Intan Safinar; Khatib, Alfi; Shaari, Khozirah; Abas, Faridah; Rukayadi, Yaya
Abstract BACKGROUND The metabolite changes in three germplasm accessions of Malaysia Andrographis paniculata (Burm. F.) Nees, viz. 11265 (H), 11341 (P) and 11248 (T), due to their different harvesting ages and times were successfully evaluated by attenuated total reflectance (ATR)–Fourier transform infrared (FTIR) spectroscopy and translated through multivariate data analysis of principal component analysis (PCA) and orthogonal partial least square–discriminant analysis (OPLS‐DA). This present study revealed the feasibility of ATR‐FTIR in detecting the trend changes of the major metabolites – andrographolide and neoandrographolide – functional groups in A. paniculata leaves of different accessions. The harvesting parameter was set at three different ages of 120, 150 and 180 days after transplanting (DAT) and at two different time sessions of morning (7:30–10:30 am) and evening (2:30–5.30 pm). RESULTS OPLS‐DA successfully discriminated the A. paniculata crude extracts into groups of which the main constituents – andrographolide and neoandrographolide – could be mainly observed in the morning session of 120 DAT for P and T, while H gave the highest intensities of these constituents at 150 DAT. CONCLUSION The information extracted from ATR‐FTIR data through OPLS‐DA could be useful in tailoring this plant harvest stage in relation to the content of its two major diterpene lactones: andrographolide and neoandrographolide. © 2014 Society of Chemical Industry